2016
DOI: 10.1016/j.bdq.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous and digital proximity ligation assays for the detection of Clostridium difficile toxins A and B

Abstract: BackgroundThe proximity ligation assay (PLA) detects proteins via their interaction with pairs of proximity probes, which are antibodies coupled to noncomplementary DNA oligonucleotides. The binding of both proximity probes to their epitopes on the target protein brings the oligonucleotides together, allowing them to be bridged by a third oligonucleotide with complementarity to the other two. This enables their ligation and the detection of the resulting amplicon by real-time quantitative PCR (qPCR), which act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The ProQuantum high-sensitivity immunoassay uses the principles of proximity-based ligation and amplification technologies to detect target antigens. , Target-specific antibodies are conjugated to oligos. When these antibodies bind to their target antigen, the oligos are brought into proximity and can be ligated to create an amplification target.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ProQuantum high-sensitivity immunoassay uses the principles of proximity-based ligation and amplification technologies to detect target antigens. , Target-specific antibodies are conjugated to oligos. When these antibodies bind to their target antigen, the oligos are brought into proximity and can be ligated to create an amplification target.…”
Section: Resultsmentioning
confidence: 99%
“…Proximity-based assays require two or more reaction components coming into proximity for a signal to be generated. Therefore, only when a binding event takes place (such as antigen–antibody binding) will the reaction components be in close enough proximity to cause a secondary reaction that results in a signal when the target of interest is present. , For example, Dhillon et al demonstrated a multistep proximity ligation assay in bulk coupled to a downstream digital PCR to detect toxins from C. difficile …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, AOCs are mainly used for detection or therapeutic applications . The detection methods include immuno-PCR (iPCR), ,, proximity ligation assay (PLA), , proximity extension assay (PEA), electrochemical proximity assay (ECPA), DNA-PAINT imaging, and protein arrays . They are based either on (a) the exceptional ability of PCR to amplify the number of DNA labels thus largely improving the detection limits or on (b) the transformation of readily accessible ON-arrays into otherwise difficult to access antibody arrays.…”
Section: Applications Of Antibody–oligonucleotide Conjugates (Aocs)mentioning
confidence: 99%
“…126 A similar approach was used by Pardridge and colleagues to prepare mAb-siRNA conjugates that showed an important (69−81%) decrease in luciferase gene expression in intracranial brain cancer in vivo. 127 The method was also applied to generate PLA probes for the detection of toxins produced by the clinically important bacterial pathogen C. diff icile 47 or to measure cytokines in a homogeneous test format with femtomolar detection sensitivities. 128 In 2014, Yin and colleagues applied AOCs to a newly developed DNA-PAINT imaging technique.…”
Section: Bioconjugate Chemistrymentioning
confidence: 99%